Case report: Obturator hernia: Diagnosis and surgical treatment - Li, Han; Cao, Xuefeng; Kong, Lingqun (Frontiers in Surgery, 2023)
Background: Obturator hernia (OH) is a rare external abdominal hernia, accounting for only 0.07-1% of all hernia cases. Because the female pelvis is wider and there is less preperitoneal adipose tissue, the obturator canal is larger, which can lead to herniation of abdominal contents when abdominal pressure increases in elderly women with thin body. The clinical symptoms of patients with obturator hernia included abdominal pain, nausea, vomiting, etc., and the mass in the inguinal region could not be touched. The positive Howship-Romberg sign is a specific sign of OH. CT is the first choice for the diagnosis of obturator hernia. Since intestinal incarceration in OH patients is prone to lead to intestinal necrosis, emergency surgical treatment is often required. However, due to the lack of specificity of its clinical manifestations, the misdiagnosis rate is high, which often leads to the delay of diagnosis and treatment. Methods: We report the case of an 86-year-old woman with a thin body and a history of multiple deliveries. The patient presented with abdominal pain, bloating, and constipation for 5 days. Physical examination revealed a positive Howship-Romberg sign on the right side, and CT examination suggested intestinal obstruction. Therefore, an urgent exploratory laparotomy was performed. Results: After opening the abdominal cavity we found that the wall of the ileum was embedded in the right obturator, and the proximal bowel was significantly dilated. We restored the embedded bowel wall to its original position, resected the necrotic bowel and performed an end-to-end anastomosis of the small intestine. The right hernia orifice was sutured, and OH was diagnosed during the operation. Conclusion: This article summarizes the diagnosis and treatment of OH by sharing this case, so as to provide a more detailed plan for early diagnosis and treatment of OH. Abbreviations: OH = obturator hernia; CT = computed tomography Keywords: Obturator hernia; case report